Clovis Mammoth Butchery: The Lange/Ferguson Site and Associated Bone Tool Technology. - Hannus, L. Aen (Texas A and M University Press : Texas A & M University Press, 2018)
Thirteen millennia ago, in a small creek valley in western South Dakota, two mammoths perished. The mammoths, an adult and a juvenile, likely a cow and calf pair, died at the edge of an ancient pond. The Lange/Ferguson site is the earliest dated archaeological site in South Dakota and one of the few North American sites that provides evidence of a Clovis-period mammoth butchering event. In addition to the preserved remains of the two mammoths, the site yielded diagnostic Clovis weaponry?three Clovis projectile points recovered in context and stratigraphically associated with the mammoth bonebed?and flaked bone tools. The site offers a rare snapshot in time detailing early Paleoindian interactions with now-extinct megafauna nearly 13,000 years ago. In Clovis Mammoth Butchery: The Lange/Ferguson Site and Associated Bone Tool Technology, L. Adrien Hannus provides a comprehensive look at one of the few New World Clovis-era sites with in-place buried deposits exhibiting evidence for an expedient bone tool technology. Multidisciplinary investigations include paleoenvironmental and geochronological reconstructions?pollen and phytoliths, geology and geomorphology, diatoms and ostracodes, mollusks, and vertebrate paleontology?as well as taphonomic evaluations and a microwear analysis of the chipped stone tools. Clovis Mammoth Butchery offers readers a rare glimpse into a singular moment in prehistory that captures human interaction with extinct animals during a rapidly changing world for which there is no modern comparison. This book shares great insight into hunting and procurement strategies used by big game hunters during the Late Pleistocene and Early Holocene.